Gas cells for tunable diode laser absorption spectroscopy employing optical diffusers. Part 1: single and dual pass cells - Hodgkinson, Jane; Masiyano, Dackson; Tatam, Ralph P. (Springer Science Business Media, 2010)
New designs for gas cells are presented that incorporate transmissive or reflective optical diffusers. These components offer simple alignment and can disrupt the formation of optical etalons. We analyse the performance-limiting effects in these cells of random laser speckle (both objective and subjective speckle), interferometric speckle and self-mixing interference, and show how designs can be optimised. A simple, single pass transmissive gas cell has been studied using wavelength modulation spectroscopy to measure methane at 1651 nm. We have demonstrated a short-term noise equivalent absorbance (NEA, 1 sigma) of 2x10(-5), but longer term drift of up to 3x10(-4) over 22 hours.
Keywords: modulation spectroscopy frequency-modulation interference-fringes hand-held speckle reduction system sensor limits noise